The L-shaped relationship between HALP score and one-year mortality in critically ill surgical patients: a retrospective cohort study - Hao Xia; Jiawei Lai; Jinzhan Lin; Zhaobin Yang; Luzhen Qiu (Scientific Reports)
Abstract The hemoglobin, albumin, lymphocyte, and platelet (HALP) score serves as a composite biomarker reflecting systemic inflammatory and nutritional status, which has demonstrated prognostic significance across various clinical conditions. This investigation specifically examines the association between HALP scores and 12-month mortality in critically ill surgical patients. Analyzing retrospective data from 8,052 patients in the Taichung Veterans General Hospital Critical Care Database, we employed nonlinear regression modeling with smooth curve fitting, threshold effect analysis, and multivariable logistic regression. The cohort demonstrated a 24.2% one-year mortality rate, with adjusted analyses revealing a nonlinear L-shaped association between HALP scores and mortality risk (p < 0.001). Below the inflection point of 44.8, each unit increase in HALP score was associated with a 2.6% reduction in mortality risk. When categorized into quartiles (Q2: 22.3–35.1; Q3: 35.2–53.9; Q4: 54.0-172.5), the adjusted odds ratios for 12-month mortality demonstrated progressive attenuation: 0.74 (95% confidence interval [CI] 0.64–0.86; P < 0.001) for Q2, 0.58 (95% CI 0.50–0.69; P < 0.001) for Q3, and 0.46 (95% CI 0.39–0.55; P < 0.001) for Q4, relative to the lowest quartile. Stratified and sensitivity analyses confirmed the robustness of these findings. This study demonstrates that lower HALP scores are associated with poorer long-term prognosis in critically ill surgical patients.